Guided tissue regeneration in patients with chronic adult periodontitis - Zuleyka Francesena Bacallao; Martha Marisel Bosch Pons (Medisur, 2017)
Foundation: periodontic care ranges from patient motivation and conventional treatments to the most sophisticated techniques of tissue engineering, among which guided tissue regeneration is a consolidated procedure in bone formation and preservation. Objective: to determine the clinical results obtained in patients who underwent a guided tissue regeneration procedure for the treatment of bone defects. Methods: a quasi-experimental intervention study of the before and after type, on patients treated at the periodontics office of Dr. Gustavo Aldereguía Lima University Hospital, from May 2014 to May 2016, with chronic adult periodontitis diagnosis and were treated with guided tissue regeneration. The sample consisted of 35 patients in whom the following clinical parameters were assessed: depth to the catheter, level of insertion of the marginal gingiva and bone level. Results: The female sex, in the ages of 35 to 59 years, was the most affected by chronic adult periodontitis and in the right and left upper molars. After treatment, a considerable reduction in depth to drilling and gain in bone level was obtained, independently of the discrete decrease in the marginal gingival insertion level. Conclusions: In patients with chronic adult periodontitis, the technique of guided tissue regeneration for the treatment of bone defects showed effectiveness according to clinical parameters obtained.